Macqueripe [sic] Bay, Trinidad, B.W.I. - (:unkn) unknown (Photos,Cum privilegio, James Books Store, 2011)
This postcard provides a view of Maqueripe Bay, a popular beach on the northern coastline of Chaguaramas which once was an American Station during World War II.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Inlets--Trinidad and Tobago; Beaches--Trinidad and Tobago; 1925; Bathing beaches--Trinidad and Tobago; Maqueripe Bay